Pengaruh Strategi Event Marketing dan Sponsorship Terhadap Brand Awareness Produk Noodle di PT. Indofood Cbp Sukses Makmur Tbk Kota Palembang - Indah Fitri Rahmawati; Roswaty Roswaty; Shafiera Lazuarni (CV. Ulil Albab Corp, 2024)
This study aims to determine how much influence the strategy of event marketing and sponsorship of brand awareness of noodle products on consumers PT. Indofood CBP Sukses Makmur Tbk Palembang the results showed that of the two promotional strategies undertaken by PT. Indofood both have a positive effect both simultaneously and partially on consumer brand awareness. By 20.1% event marketing variables can affect consumer brand awareness in remembering noodle products, while sponsorship variables affect 53.3% the remaining 26.6% are influenced by other variables that do not exist in this study. To increase consumer brand awareness of noodle products, the authors suggest that PT. Indofood CBP Sukses Makmur Tbk Palembang city prioritizes and allocates larger company funds to event marketing strategies because this strategy will attract consumers ' attention in recognizing a product and will indirectly affect their ability to remember and know what noodle products are produced by the company so that consumer brand awareness will increase.